Pseudo-septic arthritis developed after hyaluronic acid injection: A case report - Karataş, Özlem; Tuncer, Tiraje (Journal of Surgery and Medicine, 2019)
One of the most frequent causes of knee pain is knee osteoarthritis. Intra-articular hyaluronic acid (HA) injection is one of the preferred treatment methods. Although, systemic side effects are not seen, rarely local side effects as pain and swelling can be seen. Following HA injection, some cases with pseudo-septic manifestations unrelated to crystal formation have been reported. In this case report, a patient with knee pain which aggravated with medial tibio-femoral osteoarthritis refractory to conservative treatment methods including administration of non-steroidal anti-inflammatory drugs and others is presented. After intra-articular HA injection, her preexisting knee pain worsened, and swelling, and increase in local temperature were added to the clinical picture. Based on clinical, and laboratory examinations, and analysis of synovial fluid, diagnosis of pseudo- septic arthritis which mimicked manifestations of septic arthritis was made. Clinical, and laboratory improvement was achieved with early treatment. If following intra-articular HA injection, knee pain of the patient aggravates suddenly with local swelling and heat, then the possibility of pseudoseptic arthritis of the affected knee should be always kept in mind.